Natural Product Micheliolide (MCL) Irreversibly Activates Pyruvate Kinase M2 and Suppresses Leukemia - Li, Jing; Li, Shanshan; Guo, Jianshuang; Li, Qiuying; Long, Jing; Ma, Cheng; Ding, Yahui; Yan, Chunli; Li, Liangwei; Wu, Zhigang; Zhu, He; Li, Keqin Kathy; et al. (Journal of medicinal chemistry, 2018)
Metabolic reprogramming of cancer cells is essential for tumorigenesis in which pyruvate kinase M2 (PKM2), the low activity isoform of pyruvate kinase, plays a critical role. Herein, we describe the identification of a nature-product-derived micheliolide (MCL) that selectively activates PKM2 through the covalent binding at residue cysteine424 (C424), which is not contained in PKM1. This interaction promotes more tetramer formation, inhibits the lysine433 (K433) acetylation, and influences the translocation of PKM2 into the nucleus. In addition, the pro-drug dimethylaminomicheliolide (DMAMCL) with similar properties as MCL significantly suppresses the growth of leukemia cells and tumorigenesis in a zebrafish xenograft model. Cell-based assay with knock down PKM2 expression verifies that the effects of MCL are dependent on PKM2 expression. DMAMCL is currently in clinical trials in Australia. Our discovery may provide a valuable pharmacological mechanism for clinical treatment and benefit the development of new anticancer agents.